TINJAUAN YURIDIS PERJANJIAN PERKAWINAN CAMPURAN TERHADAP PEMISAHAN HARTA DAN AKIBAT HUKUMNYA - Fara Syahrial (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT Everyone who will marry commonly wants to have an everlasting and happy family. However, the marriage course will find obstacles and arise potential conflict later on. Likewise in intermarriage amongst Indonesian citizens with foreigners. They will face some problems, one of the problems are citizenship and chattel because they must obey the disparate law. Indonesian citizens must set up property separation as a precaution to protect their property rights in Indonesia by doing a marriage agreement. Based on that case so the problem can be formulated as follows; the impact and the law consequences of intermarriage, along with its urgency of a marriage agreement which relates to the property separation. This research uses juridical normative, which is done based on the prominent law proposition by studying the theories, concepts, law principle as well as the rules of statutes which correspond to this research.